Stripe-Patterned Al/PDMS Triboelectric Nanogenerator for a High-Sensitive Pressure Sensor and a Novel Two-Digit Switch with Surface-Edge Enhanced Charge Transfer Behavior - Chung-Yu Yu; Chia-Chun Hsu; Chin-An Ku; Chen-Kuei Chung (Nanomaterials)
A triboelectric nanogenerator (TENG) holds significant potential as a self-powered pressure sensor due to its ability to convert mechanical energy into electrical energy. The output voltage of a TENG is directly correlated with the applied pressure, making it highly suitable for pressure sensing applications. Among the key factors influencing TENG performance, the microstructure on the surface plays a crucial role. However, the effect of surface microstructure on charge transfer behavior remains relatively underexplored. Here, a stripe-patterned rough TENG (SR-TENG) fabricated by laser ablation and molding is proposed. The stripe-patterned rough surface exhibits excellent deformation properties, allowing for more effective contact area between the tribolayers. Additionally, the localized surface-edge enhanced electric field at the stripe boundaries improves surface charge transfer, thereby enhancing overall output performance. The SR-TENG achieved an open-circuit voltage of 97 V, a short-circuit current of 59.6 μA, an instantaneous power of 3.55 mW, and a power density of 1.54 W/m2. As an energy harvester, the SR-TENG successfully powered 150 LEDs. A linear relationship between applied pressure and output voltage was established with a coefficient of determination R2 = 0.94, demonstrating a high sensitivity of 14.14 V/kPa. For practical application, a novel self-powered two-digit pressure switch was developed based on the SR-TENG. This system enables the control of two different LEDs using a single TENG device, triggered by applying a light or hard press.